2017
DOI: 10.1038/s41598-017-02207-z
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Bt rice lines producing Cry1Ac, Cry2Aa or Cry1Ca have no detrimental effects on Brown Planthopper and Pond Wolf Spider

Abstract: Transgenic rice expressing cry genes from the bacterium Bacillus thuringiensis (Bt rice) is highly resistant to lepidopteran pests. The brown planthopper (BPH, Nilaparvata lugens) is the main non-target sap-sucking insect pest of Bt transgenic rice. The pond wolf spider (PWS, Pardosa pseudoannulata) is one of the most dominant predators of BPH in rice fields. Consequently, the safety evaluation of Bt rice on BPH and PWS should be conducted before commercialization. In the current study, two experiments were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…The results showed that the cry1Ac transgenic sugarcane lines exhibited excellent borer resistance but demonstrated genotypic differences (Table 2 and Additional file 1: Figure S1). The findings further supported that cry1Ac gene integration, whether into diploid plants such as O. sativa , or into highly complex polyploid plants such as sugarcane, can tremendously improve the resistance to borer attack [9]. In terms of agronomic performance, the transgenic sugarcane line A1 had an average cane yield of 138.79 ± 7.80 t/ha, which was almost 1.3-fold higher than that of the control sugarcane plants (FN15).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The results showed that the cry1Ac transgenic sugarcane lines exhibited excellent borer resistance but demonstrated genotypic differences (Table 2 and Additional file 1: Figure S1). The findings further supported that cry1Ac gene integration, whether into diploid plants such as O. sativa , or into highly complex polyploid plants such as sugarcane, can tremendously improve the resistance to borer attack [9]. In terms of agronomic performance, the transgenic sugarcane line A1 had an average cane yield of 138.79 ± 7.80 t/ha, which was almost 1.3-fold higher than that of the control sugarcane plants (FN15).…”
Section: Discussionmentioning
confidence: 58%
“…To date, the cry gene has been effectively used to control stem-borer pests in many crops, including rice ( Oryza sativa ) [9], corn ( Zea mays ) [10], cotton ( Gossypium hirsutum ) [11], potato ( Solanum tuberosum ) [12] and soybean ( Glycine max ) [13], which have widespread commercial applications and verified safety [1416]. There is an urgent need for borer resistance traits, and a series of studies that introduced the cry gene into sugarcane successfully obtained insect-resistant sugarcane lines [1, 4, 1719].…”
Section: Introductionmentioning
confidence: 99%
“…Improper binding of Cry toxins in the midgut of BPH and pea aphid has been known to be a possible reason for the low toxicity of these toxins ( Li et al 2011 , Shao et al 2013 , Niu et al 2017 ). Our results provide not only sequence characteristics but also structural characteristics of the CBP-like proteins of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Simon et al (2006) reported that Cry1Ab or Cry2Ab toxins did not have detrimental effects on C. carnea when ingested either directly or through prey as the larval midgut lacks specific receptors for these proteins. No prey-mediated effects of Cry proteins have also been reported in other predatory species including the coccinellids (Wu et al 2014), the rove beetles (Garcia et al 2010) and the wolf spiders (Niu et al 2017).…”
Section: Development Survival and Weight Of C Zastrowi Sillemi Fed mentioning
confidence: 99%